Respon Pemberian Pupuk N Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Varietas DXP Yangambi pada Pembibitan Main Nursery - Nitami, Dita; Sugiono, Darso; Rahayu, Yayu Sri (JURNAL AGROPLASMA, 2024)
One of the important nutrients in the process of plant growth is nitrogen (N), the provision of sufficient and balanced nitrogen nutrients can also optimize plant growth during the vegetative phase. This experiment was conducted in the Greenhouse of Singaperbangsa University Karawang campus located at Jl. HS. Ronggo Waluyo, East Telukjambe District, Karawang Regency.  The experiment was conducted from September 2023 to December 2023. The experimental method used is the experimental method, using a single-factor Randomized Group Design (RAK) consisting of 4 treatments and 6 replicates consisting of A (0.91 g/polybag), B (1.36 g/polybag), C (1.82 g/polybag), D (2.27 g/polybag). The effect of treatment was analyzed by variance analysis and if the F test at the 5% level was significant, then to find out the best treatment, it was continued with the Smallest Real Difference (BNT) further test at the 5% real level. The results achieved from this study were that there was no effect of N fertilizer application on the growth of oil palm seedlings (Elaeis guineensis Jacq.) D x P Yangambi variety in the main nursery. The treatment of N fertilizer dose in treatment B (1.36 g / polybag) gave the highest results in the parameters of plant height, number of leaflets per midrib, length of leaflets, and length of midrib but not significantly different from other treatments. Keywords: main nursery, fertilization, N fertilizer, oil palm, yangambi variety